1996
DOI: 10.1007/bf03011719
|View full text |Cite
|
Sign up to set email alerts
|

Alcalinisation des anesthésiques locaux: théoriquement justifiée mais inutile cliniquement

Abstract: On the basis of this review, routine alkalinization of local anaesthetics is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…These results are in close agreement with earlier studies that demonstrated ropivacaine and bupivacaine precipitation when they are alkalinized to physiologic pH with sodium bicarbonate, and lidocaine does not [ 9 10 11 12 ]. However, this phenomenon has not been emphasized in clinical journals or widely appreciated by physicians.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in close agreement with earlier studies that demonstrated ropivacaine and bupivacaine precipitation when they are alkalinized to physiologic pH with sodium bicarbonate, and lidocaine does not [ 9 10 11 12 ]. However, this phenomenon has not been emphasized in clinical journals or widely appreciated by physicians.…”
Section: Discussionsupporting
confidence: 92%
“…The size and number of particulates increased in the 0.2% ropivacaine mixture compared to the 0.1% mixture. These results are supported by the fact that the pKa and changed pH of the LA determine the amount of each agent presented in the basic or protonated form [20], and the concentration of the LA determines the absolute amount of each agent. In addition, this is consistent with a previous study which reported that ropivacaine at higher concentration (0.75% and 1%) forms particulates even at pH 6.0 or higher [21].…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, in theory, the alkalinization of local anesthetics can also accelerate the onset time of nerve block by increasing the proportion of non-ionized molecules. However, the use of the alkalinization technique is limited in clinical practice for its uncertain efficacy, because the precipitation generated by alkalization of local anesthetic solutions may reduce drug bioavailability [ 4 , 15 ]. The intraneural injection is an another safe and effective approach to influence the characters of the sciatic nerve block [ 16 ].…”
Section: Discussionmentioning
confidence: 99%